Effect of Fenugreek (Trigonella foenm greacum) Seed Dietary Levels on Lipid Profile and Body Weight Gain of Rats - Elmnan, Atta; Balgees, A.; Mangara, John L. (Pakistan Journal of Nutrition, 2012)
Thirty two healthy female Wister albino rats, average weight 144±5g and 3.5-4 months old were randomly divided into four groups T, TF1, TF2 and TF3 (with eight rats each). All groups were fed basal diet that contains sorghum floor, wheat bran, dry ground meat, maize oil and permix. However, TF1, TF2 and TF3 were supplemented with Fenugreek seed at 0.25, 0.50 and 0.75%, respectively. The experiment lasted for 12 weeks during which individual body weight was recorded weekly, while blood sample were collected 4 times during experimental period at weeks (6, 8, 10 and 12). Parameters measured were Total lipid, triglyceride, Low Density Lipoprotein (LDL) and High Density Lipoprotein (HDL). The results showed that fenugreek seed had a significant (P